Cytotoxic Activity, Anti-Migration and In Silico Study of Black Ginger (Kaempferia parviflora) Extract against Breast Cancer Cell - Indah Hairunisa, Indah Hairunisa; Abu Bakar, Mohd Fadzelly; Muhammad Da’i, Muhammad Da’i; Abu Bakar, Fazleen Izzany; Eka Siswanto Syamsul, Eka Siswanto Syamsul (Mdpi, 2023)
Metastatic breast cancer remains the leading cause of death in women worldwide. This condition necessitates extensive research to find an effective treatment, one of which is the natural medicine approach. Kaempferia parviflora (KP) is a plant believed to possess anticancer properties. Therefore, this study aims to determine KP’s bioactive compound, cytotoxic, and anti-migration activity in the highly metastatic breast cancer cell line model 4T1, also in the breast cancer cell model MCF-7 and noncancerous cell line NIH-3T3. Maceration with ethanol (EEKP) and infusion with distilled water (EWKP) was used for extraction. The MTT assay was used to test for cytotoxicity, and the scratch wound healing assay was used to test for the inhibition of migration. Phytochemical profiling of EEKP was performed using UHPLC-MS, and the results were studied for in silico molecular docking. Result showed that EEKP had a better cytotoxic activity than EWKP with an IC50 value of 128.33 µg/mL (24 h) and 115.09 µg/mL (48 h) on 4T1 cell line, and 138.43 µg/mL (24 h) and 124.81 µg/mL (48 h) on MCF-7 cell line. Meanwhile, no cytotoxic activity was observed at concentrations ranging from 3–250 µg/mL in NIH-3T3. EEKP also showed anti-migration activity in a concentration of 65 µg/mL. Mass Spectrophotometer (MS) structures from EEKP are 5-Hydroxy-7,40 -dimethoxyflavanone (HDMF), 5-Hydro-7,8,20 -trimethoxyflavanone (HTMF), Retusine, and Denbinobin. The in silico docking was investigated for receptors Bcl-2, Bcl-XL, ERK2, and FAK, as well as their activities. In silico result indicates that HTMF and denbinobin are bioactive compounds responsible for EEKP’s cytotoxic and anti-migration activity. These two compounds and standardized plant extract can be further studied as potential breast cancer treatment candidates.